Implementasi Nilai Disiplin dan Istiqomah melalui Pembiasaan Muroja’ah Program Tahfidz di MI Terpadu Tahfidzul Qur’an Surakarta - Kinesti, Rakanita Dyah Ayu; Fatmala, Riska; Dewi, Annisya Aulia; Husna, Maulidiah (Lembaga Yasin AlSys, 2023)
Studying the tahfidz of the Qur'an is currently being carried out very relevant to be raised. Many Islamic learning institutions in Indonesia are currently activating and expounding the tahfidz Al-Qur'an program. This situation shows the high enthusiasm of Indonesian Muslims for memorizing the Qur'an and sending their children to memorize the Al-Qur'an. This tendency is also an indication of I'tikad in Islamic learning. Although actually memorizing the Al-Qur'an is not something actual for adherents of Islam, the memorization of the Al-Qur'an has been taking place in Islamic boarding schools for a long time. The topic of this observation is from school or madrasa principals, caregivers of the taḥfiz program, taḥfizz tutors, students and parents. The material for this observation is Mittqum Surakarta. The method of accumulation of evidence is through observation, interviews, and archiving. Sharpness is defined as well as accuracy. This research uses its type, namely qualitative, which also requires a descriptive approach. The existence of the origin of the data obtained from humans, locations, and minutes obtained from the field, how to collect information by observation and documentation. The method of data analysis requires correct data, submission of data, and retrieval of results. The linguistic method of the reviewer's data uses technical triangulation, original triangulation, and opportunity triangulation. Observations show that the implementation of the character values of discipline and istiqomah emerges through muroja'ah habituation carried out by the ustadzah before continuing new memorization.